Feijão-caupi: parâmetros produtivos, biométricos, fisiológicos, bioquímicos e prospecção de genes, frente ao aumento da temperatura e do deficit hídrico - Barros, Juliane Rafaele Alves Barros (2021)
The selection of tolerant cowpea (Vigna unguiculata L.) cultivars is of great importance to ensure greater productivity in the face of climate change. Thus, the objective was to evaluate how the increase in temperature and water deficit affect the biometric, productive, physiological, biochemical, and molecular parameters of different cowpea cultivars. The experiments were carried out in a germination chamber, growth chambers and greenhouse, using different cowpea cultivars, which were subjected to increased temperatures and different water availability. The cultivars respond differently to these stresses, with physiological, biochemical, molecular changes and variation in the final production. The percentage of germination of cowpea seeds reaches values above 90%, in the range of 20-40 ° C. However, at a temperature of 40 ° C, normal seedlings do not occur. The cultivars differ from each other in view of the increase in temperature. Through the combination of biometric, physiological, and productive responses to cultivate Itaim showed greater tolerance to the increase of 4.8 ° C in air temperature. The flowering phase was the most sensitive to temperature increase and water deficit, with a significant reduction in production. Temperature is the determining climatic element for choosing the planting season, because even with 100% water availability, the increase in temperature reduces production. P5CR and TPS6 genes, belonging to different classes of osmoprotectors, were induced in cowpea, cv. Carijó in response to rising temperatures and severe drought